Epidemiological Profile of Patients with Cutaneous Melanoma in a Region of Southern Brazil - Marcelo Moreno; Ricardo Ludwig Schmitt; Maria Gabriela Lang; Vanessa Gheno (Journal of Skin Cancer)
Cutaneous melanoma (CM) is responsible for 75% of deaths from malignant skin cancer. The incidence of CM in the southern region of Brazil, particularly in the western region of Santa Catarina, is possibly higher than estimated. In this study, the clinical and epidemiological profile of patients with CM treated in the western region of Santa Catarina was examined. A cross-sectional study was performed with patients diagnosed with CM from January 2002 to December 2009, from 78 counties of the western region of the state of Santa Catarina. Data were collected using a protocol adapted from the Brazilian Melanoma Group and 503 patients were evaluated. The incidence and prevalence of CM found in this region are much higher than those found elsewhere in the country. This fact is most likely due to the phenotypic characteristics of the population and the high incidence of UV radiation in this region due to its location in southern Brazil, as is the case in the countries of Oceania.